(untitled) (REMUNOM, 2024)
Introduction: around 95% of maternal deaths worldwide could have been avoided if health services expanded women’s sexual and reproductive rights, guaranteeing safe care at all times during pregnancy, childbirth and the postpartum period. Theoretical basis: Maternal mortality refers to any death that occurs during the gestational period or after 42 days of its end, regardless of location or duration, with the main cause being the condition. Strategies were developed to reduce maternal mortality and increase understanding of the social determinants that lead to the deaths of these patients. From this point on, maternal mortality began to be understood as an indicator of social development and its reduction was included as one of the goals of the Millennium Development Goals (MDG) and Sustainable Development Goals (SDG). Methodology: This article is exploratory, descriptive, retrospective in nature, through data collection on the public page of the Department of Informatics of the Unified Health System (DATASUS). Analysis and discussion of results: It was observed that, in short, deaths occurred in the postpartum period (71.42%); no hospital (100%); the age group from 30 to 39 years old predominates (71.42%); of women with 8 to 11 years of education (42.75%); married, (35.71%); and white, (64.28%). Conclusion: the maternal mortality rate in Cascavel-PR meets the Brazilian target and is evidenced by white women, aged 30 to 39 years, married, with up to 11 years of schooling, whose death is due to direct or indirect causes equally, during the postpartum period of cesarean deliveries in a hospital environment. KEYWORDS: maternal mortality, maternal death, live-births.